Recent applications of computational methods to allosteric drug discovery - Govindaraj, Rajiv Gandhi; Thangapandian, Sundar; Schauperl, Michael; Denny, Rajiah Aldrin; Diller, David J. (Frontiers in Molecular Biosciences, 2023)
Interest in exploiting allosteric sites for the development of new therapeutics has grown considerably over the last two decades. The chief driving force behind the interest in allostery for drug discovery stems from the fact that in comparison to orthosteric sites, allosteric sites are less conserved across a protein family, thereby offering greater opportunity for selectivity and ultimately tolerability. Significant challenges remain, however, to turn the interest in allostery to beneficial therapeutics. These include identifying allosteric sites that can significantly impact the function of the protein, understanding the mechanism of allostery so that meaningful in vitro assays can be developed and finding sufficiently potent chemical matter for the shallow and superficial sites that are common to allostery. All three of these challenges open several interesting theoretical and computational questions. Here we highlight recent progress and remaining challenges for computational methods in allosteric drug design.